PENERAPAN METODE ROLE PLAYING DALAM MENINGKATKAN KEAKTIFAN SISWA PADA MATA PELAJARAN PAK (Study Kasus: SD I Haruku-Sameth) - Melda Pasalbesy (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2019)
The purpose of this class action study is to determine the influence of Role Playing in the activity of child learning and outcomes at SD I Haruku School. The method in this research is the method of class action research, based on the results of the study, it can be concluded that the implementation of Role Playing methods can improve the activity and learning outcomes of children in the learning process. In addition, research results can also be advice as well as consideration materials for both teachers and school to create a learning atmosphere that provides a lot of space for students to engage actively at the time of study, where students are no longer Learn by simply being a listener, but through the application of a role Playing method, both teachers, students, and school parties can create active and enjoyable learning on the subject of Christian religious education.Keyword: Role Playing, student activity